(untitled) (Journal of the College of Basic Education, 2022)
Was Determinate concentrations of Citric acid (Cit.A), Acetic acid (Ac.A), Ascorbic acid (As.A), Sodium chloride NaCl, Caffeine (Caff), sugar and dye caramel and some trace elements (iron, copper, zinc, manganese, aluminum and lead) in soft drinks and juices deployed in Iraqi market various analytical ways Volumetric Analysis and High Performance Liquid Chromatography was written way sugar estimate between (0-25)% and elements (iron, copper, zinc, manganese, aluminum, lead) (2.5-14)ppm, (1-8 )ppm, (0.5-3)ppm, (1-8)ppm, (10-60)ppm, (12-80)ppm respectively. The estimated amount of material in the soft drinks and juices ranged (0-1.601)%, (0-1.5)%, (1.357-16.266)%, (22-176) mg/100ml, (58.4-876) mg/kg and (0 -12161.84) mg/L materials measured (Citric acid, Acetic acid, Sugar, Ascorbic acid, Sodium chloride, Caffeine) respectively. It has been found that many of the models in which additives have exceeded the permissible limits.